The formation of IIE iron meteorites investigated by the chondrule‐bearing Mont Dieu meteorite. (25th June 2015) - Van Roosbroek, N.; Debaille, V.; Pittarello, L.; Goderis, S.; Humayun, M.; Hecht, L.; Jourdan, F.; Spicuzza, M. J.; Vanhaecke, F.; Claeys, Ph.
Abstract A 435 kg piece of the Mont Dieu iron meteorite (MD) contains cm‐sized silicate inclusions. Based on the concentration of Ni, Ga, Ge, and Ir (8.59 ± 0.32 wt%, 25.4 ± 0.9 ppm, 61 ± 2 ppm, 7.1 ± 0.4 ppm, respectively) in the metal host, this piece can be classified as a IIE nonmagmatic iron. The silicate inclusions possess a chondritic mineralogy and relict chondrules occur throughout the inclusions. Major element analysis, oxygen isotopic analysis (Δ17O = 0.71 ± 0.02‰), and mean Fa and Fs molar contents (Fa15.7 ± 0.4 and Fs14.4 ± 0.5) indicate that MD originated as an H chondrite. Because of strong similarities with Netschaëvo IIE, MD can be classified in the most primitive subgroup of the IIE sequence. 40Ar/39Ar ages of 4536 ± 59 Ma and 4494 ± 95 Ma obtained on pyroxene and plagioclase inclusions show that MD belongs to the old ( 4.5 Ga) group of IIE iron meteorites and that it has not been perturbed by any subsequent heating event following its formation. The primitive character of MD sheds light on the nature of its formation process, its thermal history, and the evolution of its parent body.